2017
DOI: 10.1039/c6ay02472f
|View full text |Cite
|
Sign up to set email alerts
|

Rapid determination of the Mn average oxidation state of Mn oxides with a novel two-step colorimetric method

Abstract: The Mn average oxidation state (Mn AOS) of Mn oxides has a significant impact on their reactivity towards trace metals and organic contaminants via sorption, catalysis and oxidation processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…S2), a color typical for Mn(III)-PP (Qian et al, 2019). High-valent Mn in solution, which hereafter refers to Mn(III)-PP, was quantified using Leucoberbelin Blue I (Zhu et al, 2017). The similar increases of aqueous Mn and of Mn(III)-PP indicated that Mn in solution was overwhelmingly trivalent and present as Mn(III)-PP (Fig.…”
Section: The Oxidation Of As(iii) By Birnessite With/without Chelating Agentsmentioning
confidence: 98%
“…S2), a color typical for Mn(III)-PP (Qian et al, 2019). High-valent Mn in solution, which hereafter refers to Mn(III)-PP, was quantified using Leucoberbelin Blue I (Zhu et al, 2017). The similar increases of aqueous Mn and of Mn(III)-PP indicated that Mn in solution was overwhelmingly trivalent and present as Mn(III)-PP (Fig.…”
Section: The Oxidation Of As(iii) By Birnessite With/without Chelating Agentsmentioning
confidence: 98%
“…Although Mn AOS of birnessite has been extensively measured using redox titration or X-ray absorption near-edge spectroscopy (XANES) [40], XPS can provide information about AOS changes specifically on the surface or in the near-surface region of birnessite after reaction with aqueous Mn 2+ at a lower concentration range. Figure 3a shows the survey scan of the as-synthesized birnessite.…”
Section: Aos Of Birnessite After Reaction With Aqueous Mn(ii)mentioning
confidence: 99%
“…For O 1s, an example of the calculation is provided in the Supporting Information section (Table S1) and calculates a value of +3.5. The bulk AOS was determined by a chemical titration method, which involves reaction of oxalic acid with the sample and then back-titration by KMnO 4 , 46 which determined AOS of +3.2. The AOS from the three methods averages to +3.4.…”
Section: Resultsmentioning
confidence: 99%